Web-Based Information and Reservation Media for VW Safari Borobudur - Fatkhurrochman Fatkhurrochman; Riska Dwi Handayani; Yeza Febriani; Tri Yusnanto (International Journal of Computer and Information System (IJCIS), 2023)
Borobudur is one of the most popular tourist objects in Indonesia. Borobudur is located in Magelang Regency. Borobudur District is a center for tourism and MSME development that is able to attract the attention of both local and foreign tourists. VW Safari Magelang is one of the experienced tour guide service providers offering a complete tour package, including lodging information, Borobudur special food and other facilities around Borobudur tourist attractions. The lack of information media owned resulted in the VW Safari Borobudur being less well known. This research produces information media and website-based reservations to increase tourists' knowledge and interest in VW Safari Borobudur. In designing information media using UML with system development using the waterfall process model. To build information and reservation media, PHP and MySQL programming languages are used and the Codeigniter framework is used